Wakinyan : Lakota religion in the twentieth century - Feraca, Stephen E., 1934- (Lincoln : University of Nebraska Press, 1998)
Wakinyan is an excellent overview of Lakota religious thought and practice, introducing readers to its essential components. Through finely detailed descriptions of rituals and various types of religious figures, Stephen E. Feraca explains the significance of such practices as the Sun Dance, sweat lodge ritual, vision quest, Yuwipi ritual, and peyote use. He also discusses the significance of herbs and religious artifacts and objects and explains the roles and responsibilities of medicine men and other religious practitioners.
First written as a report for the Department of the Interior in 1963, Wakinyan has long been recognized as a classic study of Lakota religion. This edition retains most of the original text, with its first-rate ethnographic descriptions of religious practices. The author's new endnotes bring the reader up to date on changes in Lakota religion during the last three decades.
Brief history of the Lakotas -- Sun dance -- Vision quest -- Yuwipi -- Other ceremonies and practices -- Peyotism -- Herbalism.
Includes bibliographical references (pages 93-104).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Lakota Indians -- Religion; Lakota -- Religion; RELIGION -- Ethnic & Tribal; Lakota Indians -- Religion; Ethnic & Race Studies; Gender & Ethnic Studies; Social Sciences; Teton (Indiens) -- Religion